WILLINGNESS TO PAY FOR TOURISTS TAX IN PREMIUM DESTINATIONS: LABUAN BAJO CASE STUDY - Reynaldo Angga Siagian; Ni Wayan Noviana Safitri; Thyophoida W. S. Panjaitan (International Journal of Financial and Investment Studies (IJFIS), 2022)
The government is trying to break away from dependence on the exploitation of natural resources, so in recent years, it has focused on tourism. The Covid-19 pandemic has greatly impacted the tourism sector, but in 2022 the level of foreign tourist visits to Indonesia is slowly starting to improve. Labuan Bajo is one of the areas targeted by the government to be developed in the tourism sector to make premium destination spots, in supporting the existence of tourism, various infrastructures are built so that they can become world-class destinations. In addition, Labuan Bajo also offers natural tourism products that require sustainability to maintain their natural habitat and certainly require considerable costs in conducting regular monitoring and maintenance. The existence of high development and operational costs, the government needs to find ways to obtain optimal state revenue, especially in terms of taxes charged to tourists. The revenue obtained from the tourism tax is a very important financial source for the government and tourism authorities to ensure the sustainability of the tourism sector and can improve the quality of destinations given to visitors to tourist attractions. In an effort by tourism policymakers to create an efficient and fair tax system in tourist destinations, it is very important to understand tourists' perceptions of willingness to pay (WTP), tax rates, and optimal allocation. This research is a qualitative study, and the purpose of this study is to evaluate the tourism tax charged to tourists as compensation to get optimal regional income and to measure the willingness to pay tourists. The ability to pay is necessary to know how much the government can attract taxes to get optimal local revenue but not be too burdensome for tourists. This research will also explore tourist perceptions regarding taxes and what things need to be developed so that absorption from state and regional budgets can be effective in developing destination areas, especially in a sustainable manner. The approach used in data collection using semi-structured in-depth interviews with international tourists visiting Labuan Bajo, East Nusa Tenggara. This research is expected to be used by policymakers to understand the optimal value of tourism taxes to be able to develop their regions.